Thirteen bisbenzylisoquinoline alkaloids in five Chinese medicinal plants: Botany, traditional uses, phytochemistry, pharmacokinetic and toxicity studies. (25th March 2021) - Zhang, Han; Wang, Xiaoming; Guo, Yaqing; Liu, Xiaomei; Zhao, Xizi; Teka, Tekleab; Lv, Chunxiao; Han, Lifeng; Huang, Yuhong; Pan, Guixiang
Abstract: Relevance: Bisbenzylisoquinoline (BBIQ) alkaloids are generally present in plants of Berberidaceae, Monimiaceae and Ranunculaceae families in tropical and subtropical regions. Some species of these families are used in traditional Chinese medicine, with the effects of clearing away heat and detoxification, promoting dampness and defecation, and eliminating sores and swelling. This article offers essential data focusing on 13 representative BBIQ compounds, which are mainly extracted from five plants. The respective botany, traditional uses, phytochemistry, pharmacokinetics, and toxicity are summarized comprehensively. In addition, the ADME prediction of the 13 BBIQ alkaloids is compared and analyzed with the data obtained. Materials and methods: We have conducted a systematic review of the botanical characteristics, traditional uses, phytochemistry, pharmacokinetics and toxicity of BBIQ alkaloids based on literatures collected from PubMed, Web of Science and Elsevier during 1999–2020. ACD/Percepta software was utilized to predict the pharmacokinetic parameters of BBIQ alkaloids and their affinity with enzymes and transporters. Results: Botany, traditional uses, phytochemistry, pharmacokinetic and toxicity of 13 alkaloids, namely, tetrandrine, dauricine, curine, trilobine, isotrilobine, cepharanthine, daurisoline, thalicarpine, thalidasine, isotetrandrine, liensinine, neferine and isoliensinine, have been summarized in this paper. It can't be denied that these alkaloids are important material basis of pharmacological effects of family Menispermaceae and others, and for traditional and local uses which has been basically reproduced in the current studies. The 13 BBIQ alkaloids in this paper showed strong affinity and inhibitory effect on P-glycoprotein (P-gp), with poor oral absorption and potent binding ability with plasma protein. BBIQ alkaloids represented by tetrandrine play a key role in regulating P-gp or reversing multidrug resistance (MDR) in a variety of tumors. The irrationality of their usage could pose a risk of poisoning in vivo, including renal and liver toxicity, which are related to the formation of quinone methide during metabolism. Conclusion: Although there is no further clinical evaluation of BBIQ alkaloids as MDR reversal agents, their effects on P-gp should not be ignored. Considering their diverse distribution, pharmacokinetic characteristics and toxicity reported during clinical therapy, the quality standards in different plant species and the drug dosage remain unresolved problems.